On the expansion schemes in trajectory reversing method - Măruşter, Ştefan (Rev. Anal. Numér. Théor. Approx., 2002)
The paper deals with certain expansion schemes in trajectory reversing method for estimating asymptotic stability region of nonlinear dynamical systems. The asymptotic behavior of the sequence of estimates is investigated. Some numerical examples are given.